Pengaruh Latihan Lari Zig – Zag Menggunakan Beban Terhadap Peningkatan Keterampilan Dribbling dalam Permainan Sepak Bola Pada Siswa Ekstrakurikuler SMA Negeri 4 Seluma - beni novsir; defliyanto defliyanto; Yarmani Yarmani (SPORT GYMNASTICS : Jurnal Ilmiah Pendidikan Jasmani, 2020)
This study aims to determine the effect of Zig-Zag Running Exercise Using Loads on Improving Dribbling Skills in Football Games for Extracurricular High School Students in Seluma State High School 4. This type of research used in this research is quantitative research Experiment One Group Pretest-Postest Design. The population in this study were all extracurricular activities in SMA NEGERI 4 Seluma, amounting to 30 people. The results of the study of the Effect of Zig-Zag Running Exercise Using Load Against Improvement of Dribbling Skills in Football Games in Extracurricular High School Students of Seluma 4 Seluma obtained pretest results of 44.03 and posttest average results of 46.3 with a difference of 2.27 and the results of t count is 1,738> from t table 1,699. Based on statistical tests with ? = 5% (0.05) that H0 is rejected or Ha is received systematically that Zig-Zag Running exercises affect Dribbling skills.